2014
DOI: 10.1007/s12013-014-0328-3
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Hepatoprotective and Antioxidant Role of Walnuts Against Ethanol-Induced Oxidative Stress in Rats

Abstract: The aims of our study were the evaluation of the hepatoprotective effect and antioxidant role of walnuts against ethanol-induced oxidative stress. The hepatoprotective and antioxidant role of the walnuts supplementation feed against ethanol-induced oxidative stress were evaluated by measuring liver damage serum marker enzymes; aspartate aminotransferase (AST); alanine aminotransferase (ALT); gamma glutamyl transpeptidase (GGT); lactate dehydrogenase (LDH); and antioxidant defense systems such as reduced glutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…Conversely, our results demonstrate that JRVO protect from oxidative damage by stabilizing the enzyme levels (AST, ALT, ALP, LDH) indicating a protective role for this oil against liver dysfunctions. Similar findings were reported earlier upon Juglans extract but not Juglans oil against CCl4‐induced hepatotoxicity or against ethanol‐induced hepatotoxicity in rats …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Conversely, our results demonstrate that JRVO protect from oxidative damage by stabilizing the enzyme levels (AST, ALT, ALP, LDH) indicating a protective role for this oil against liver dysfunctions. Similar findings were reported earlier upon Juglans extract but not Juglans oil against CCl4‐induced hepatotoxicity or against ethanol‐induced hepatotoxicity in rats …”
Section: Discussionsupporting
confidence: 91%
“…Similar findings were reported earlier upon Juglans extract but not Juglans oil against CCl4-induced hepatotoxicity 8 or against ethanol-induced hepatotoxicity in rats. 46 Lipids play an important role in hepatic disease incidence because they form cell membranes and several hormones in healthy bodies. In our study, administration of lead acetate was found to cause significant elevation in TG, TC, LDL cholesterol levels, TC/HDL-C, LDL-C/ HDL-C ratio, with a concomitant decrease of HDL-C attributed to dyslipidaemia, as well as increase of lipase activity.…”
Section: Effects Of Vegetable Oil (Jrvo) On Hepatic Tissuesmentioning
confidence: 99%
“…It is well known that aldehydes and ROS can directly affect both proteins or DNA, leading to transcription-repression of concrete genes. In fact, the role of ROS and aldehydes seems to be a key factor for these alterations, partially confirmed by the fact that administration of antioxidants prevents these EtOH-induced cellular alterations (Herrera et al, 2003; Bati et al, 2015; Han et al, 2015). …”
Section: General and Local Etoh Metabolism: Oxidative Stress And Etohmentioning
confidence: 91%
“…Group Ⅰ (n =10, normal group): mice were treated by gavage with normal saline at a dose of 10 mL/kg twice a day with an interval under 2 h. Group Ⅱ (n =10, alcohol-treated group): mice received 28% (v/v) ethanol (10 mL/kg BW) 2 h after normal saline by intragastric gavage (10 mL/kg BW). Groups III (n =10) and IV (n =10) are dose-dependent test groups, where mice were administered by intragastric gavage with 28% (v/v) ethanol (10 mL/ kg BW) 2 h after administration of CGMCC 3917 bacterial suspension by intragastric gavage at a dose of 10 mL/kg BW (Bati, Celik, & Dogan, 2014). The concentrations of bacterial suspension were approximately 2 ×10 8 (highdose group) and 2 ×10 6 CFUs (low-dose group), respectively.…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…The activities of AST, ALT, and ALP in the serum are considered as reliable and sensitive indicators of ALD (Bati et al, 2014;Uyanoglu et al, 2014). AST and ALT are enzymes present in hepatocytes, and these intracellular enzymes are released into the circulation when injury is induced in the liver (Wang et al, 2014).…”
Section: Effects Of Strain Cgmcc 3917 On Serum Aminotransferase Activmentioning
confidence: 99%